Pengaruh Return on Assets (ROA) dan Non Performing Loan (NPL) terhadap Financial Sustainability pada Sektor Perbankan di Bursa Efek Indonesia dengan Variabel Moderating Kepemilikan Institusional Tahun 2019–2023 - Nahya Shaffa Alyara; Lasmanah; Meirani, Nadia (Bandung Conference Series: Business and Management, 2024)
Abstract. This research aims to examine the influence of Return on Assets (ROA) and Non-Performing Loans (NPL) on Financial Sustainability, moderated by Institutional Ownership in the banking sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This is a quantitative study with a descriptive-verificative approach. The sample was selected using purposive sampling, resulting in 16 banks listed on the IDX over a five-year period. This study employs panel data regression analysis and moderation regression analysis. The results of the tests indicate that, simultaneously, ROA, NPL, and institutional ownership have a significant effect on the financial sustainability ratio. However, partially, ROA does not have a significant effect on the financial sustainability ratio, while NPL has a significant effect on the financial sustainability ratio. Institutional ownership insignificantly strengthens the influence of ROA on the financial sustainability ratio. Moreover, institutional ownership can significantly strengthen the relationship between ROA and the financial sustainability ratio. Abstrak. Penelitian ini memiliki tujuan untuk menguji pengaruh ROA dan NPL terhadap Financial Sustainability yang dimoderasi oleh Kepemilikan Institusional pada sektor perbankan di Bursa Efek Indonesia (BEI) tahun 2019 – 2023. Jenis penelitian kuantitatif dengan pendekatan deskriptif verifikatif. Pengambilan sampel menggunakan metode purposive sampling dan diperoleh 16 perbankan yang terdaftar di BEI dengan periode penelitian 5 tahun. Pada penelitian ini menggunakan analisis regresi data panel dan analisis regresi moderasi. Hasil dari pengujian menjelaskan secara simultan ROA, NPL, dan kepemilikan institusional berpengaruh signifikan terhadap financial sustainability ratio. Sedangkan secara parsial ROA tidak berpengaruh signifikan terhadap financial sustainability ratio, sementara NPL berpengaruh signifikan terhadap financial sustainability ratio. Adapun kepemilikan institusional memperkuat pengaruh ROA terhadap financial sustainability ratio secara tidak signifikan. Kemudian kepemilikan institusional dapat memperkuat pengaruh antara ROA terhadap financial sustainability ratio secara signifikan.